AFGHAN DOMESTIC WOMEN AS REPRESENTED IN KHALED HOSSEINI’S A THOUSAND SPLENDID SUNS AND ATIQ RAHIMI’S THE PATIENCE STONE - Yeni Probowati (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2017)
This paper aims to describe Afghan domestic women and the impact of maleoppressionover them. The research uses qualitative approaches with feminism theory, especially radical feminism. The data are taken from thenovels, Khaled Hosseini's A Thousand Splendid Suns and AtiqRahimi'sThe Patience Stone. In A Thousand Splendid Suns Mariam and Lailaare described as Afghan women are oppressed, powerless, marginalized and exploited in the domestic area. The impact of male domination are depression, anxiety,trauma and death either to the oppressor or the oppressed. This leads to the rejection against the dominancein the form of the struggle for freedom. In The Patience Stone, a female character whose name is unknown, experiencing violence in the household. Her husband does physical violence, sexual harassment and mental abuse. This caused her to be frustrated, depressed and traumatized.A tragic moment ends the story as the fruit of mal oppression against Afghan women in the domestic area, namely the desire to kill their husbands. From the portrait of women in Afghanistan as told by KhaledHosseini and AtiqRahimi, a moral value that can be drawn is a patriarchal system of society should be eliminated. Because of the patriarchal system, it will become the beginning of the maledominance to women in domestic area in this case their wives and daughters. Women should be treated as a partner in joy and sorrow. They are not considered as a slave or an outlet for their anger and desire.